Development and analysis of an automated performance code checking workflow - Arantes, Eduardo; Andery, Paulo Roberto Pereira; Andrade, Flávio; Paes, Daniel; Irizarry, Javier (Ambiente Construído, 2022)
This study aimed to evaluate the applicability, accuracy, and challenges involved in the automated checking of design requirements specified by a Performance Code (PC) using a BIM (Building Information Modeling)-enabled model checker software application. Specific goals include: (a) definition of a workflow for the parameterization of a set of computational rules addressing part of the PC design requirements, (b) testing and evaluation of the proposed parameterization using a BIM model of a real large-scale housing project, and (c) comparison of accuracy and checking times between manual and automated methods. The research team developed and tested the automated checking of approximately one-third of the requirements. Findings indicate a substantial checking time decrease and an increase in the number of nonconformities detected through the automated method in comparison to the traditional technique of compliance assessment.